JUAN RAFAEL ALLENDE’S ¿WANDERINGS INTO THE CITY OF ‘MARBLE PALACES’ AND DELIGHTFUL CASSEROLES. SANTIAGO OF CHILE, 1880-1910. - Palma Alvarado, Daniel (Revista de Historia Social y de las Mentalidades, 2011)
This article deals with a chapter of the social and urban history of Santiago de Chile, throughout a period in which the city was subject of deep changes that modified its colonial setting and long lasting social relationships. Following the sharpness of the satiric writer Juan Rafael Allende, we look to the insuficiencies of the urbanizing process, the new characters ocupying the city’s squares and streets, as well as the multiple entertainments animating the everyday life of its inhabitants.